Elementary School Pre-Teacher Prospective on the Application of HOTS-Based Questions in Improving Analytical Critical Thinking Ability in Science Lessons - Siti Fatimah (MISOOL: Jurnal Pendidikan Dasar, 2024)
Critical thinking skills are still very low in the Southwest Papua region. This can be said because students still tend to answer questions according to what they read in books rather than from their own thoughts. To improve critical thinking skills, it is necessary to get used to it or give HOTS-based questions to students. HOTS-based questions are designed to determine students' critical thinking abilities. The aim of the research carried out by researchers was to find out the opinions of prospective teachers regarding the application of HOTS-based questions in science learning in elementary/MI. The method used in the research that the researchers conducted was descriptive qualitative. The data collection technique used was through tests and interviews with 18 prospective teacher students. The data analysis technique used is a qualitative analysis technique with four stages, namely data collection, data reduction, data display and conclusion drawing. The results of the research conducted by researchers are: 1) prospective teacher students agree with the application of HOTS-based questions in improving critical thinking skills in science lessons in elementary/MI; 2) student teachers said that the main advantage of HOTS-based questions is that they can improve high-level thinking and critical thinking skills; 3) the application of HOTS-based questions is suitable for high classes, namely grades 4-6 SD/MI; 4) application of HOTS-based questions can improve critical thinking skills; 5) implementing HOTS-based questions can improve the quality of education in Indonesia. It can be concluded that according to student teachers, the application of HOTS-based questions is very good and has benefits and impacts on education in Indonesia.